The protection of internaly displaced persons by international migration law - Eveline Vieira Brigido (Universidade de Santa Cruz do Sul, 2018)
This paper aims to analyze how international migration law protects internally displaced persons. First of all, there is a general approach about the history of International Regulations of migrations and about the concept of displaced person. Afterwards, it will be analyzed today’s regulation of displaced persons by International Law. At the end, it is concluded that there are a few legal documents that protect these persons, and internationally there are only the Guiding Principles. Although all these principles are foreseen in many human rights treaties, new legal documents should be developed for the adequate protection of internally displaced persons.